Efficacy testing of the SAVOR (Sisters Adding Fruits and Vegetables for Optimal Results) intervention among African American women: A randomized controlled trial - LaVonne Brown; Manoj Sharma; Sophia Leggett; Jung Hye Sung; Russell L. Bennett; Mario Azevedo (Tabriz University of Medical Sciences, 2020)
Background: In the United States, only about 15% of individuals meet daily fruit intake recommendations of 2 cups per day and only 10% meet the vegetable intake recommendations of 3 cups per day. African American women are a high-risk group. In this study, a fourth-generation multi-theory model (MTM) of health behavior change was used to design and evaluate a Sisters Adding Fruits and Vegetables for Optimal Results (SAVOR) intervention for AA women. Methods: The study utilized a randomized controlled trial (RCT) with measurements taken at pretest, posttest (after the three-week intervention) and follow-up (at the end of eight weeks). SAVOR (n=26) was compared to an equivalent knowledge-based intervention (n=28). Process evaluation was done for program fidelity and satisfaction. A validated 38-item self-reported questionnaire was used to measure changes in MTM constructs and past 24-hour consumption of fruits and vegetables. Results: The SAVOR intervention resulted in improvement of mean consumption of fruits and vegetables in the experimental group from pre-test (2.78) to posttest (4.77) to recommended levels at follow-up (5.04) while in the comparison group they remained at around 3 (P<0.0001) Statistically significant changes (P<0.05) were noted for all MTM constructs except for participatory dialogue. Conclusion: The SAVOR intervention was found to be efficacious and established the robustness of MTM. SAVOR can be replicated for future effectiveness trials.